Trigonelline and curcumin alone, but not in combination, counteract oxidative stress and inflammation and increase glycation product detoxification in the liver and kidney of mice with high-fat diet-induced obesity - Costa, Mariana Campos [UNESP]; Lima, Tayra Ferreira Oliveira [UNESP]; Arcaro, Carlos Alberto [UNESP]; Inacio, Maiara Destro [UNESP]; Batista-Duharte, Alexander [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Spolidorio, Luís Carlos [UNESP]; Assis, Renata Pires [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Baviera, Amanda Martins [UNESP] (Elsevier, 2020)
The development of obesity-associated complications is related to various pathogenic events including chronic inflammation, oxidative stress and generation of advanced glycation end products (AGEs). Due to their antioxidant, anti-inflammatory and antiglycation properties, trigonelline and curcumin are interesting candidates to counteract complications of obesity and diabetes mellitus. The current study aimed to investigate the effects of treatment with curcumin or trigonelline mixed into yoghurt, alone or in combination, on mice fed high-fat diet (HFD); the focus was mainly on the potential of these phytochemicals to counteract oxidative and glycative stress. Yoghurt alone improved glucose tolerance and reduced proinflammatory cytokine levels in HFD mice; however, it did not affect the antioxidant status. Trigonelline-enriched yoghurt prevented fat accumulation in adipose tissue, improved both insulin sensitivity and glucose tolerance and exerted anti-inflammatory and antiglycation activities (reduced AGEs and AGE receptor levels and increased the levels of components related to AGE detoxification) in liver and kidney of HFD mice. Curcumin-enriched yoghurt exerted anti-inflammatory and potent antioxidant properties (increased antioxidant enzyme activities and decreased lipid peroxidation) in liver and kidney of HFD mice. However, several beneficial effects were nullified when trigonelline and curcumin were administered in combination. Trigonelline and curcumin have emerged as promising complementary therapy candidates for liver and kidney complications associated with obesity. However, the administration of these phytochemicals in combination, at least in HFD mice, was not effective; inhibition of biotransformation processes and/or the reaching of toxic doses during combined treatment may be prevailing over the individual pharmacodynamic actions of these phytochemicals.
Keywords: Advanced glycation; Curcumin; Inflammation; Obesity; Oxidative stress; Trigonelline